Development of Learning Models in Core Competency Practice Courses Department of Mechanical Engineering Education Manado State University - Mumek, Fillyen; Oroh, Rolly Robert; Tamba, Ibadja P. (International Journal of Information Technology and Education, 2023)
The learning process obtained from universities to develop students' soft skills is also influenced by practical experience in the field. To develop soft skills in students, they have been given theories and practices that support the lessons in higher education, so that students have experience that can be used as a basis when entering the world of work. This research aims to develop a practical learning model in the Department of Mechanical Engineering Education, Manado State University. This research is developing research to develop a practical learning model. The online practice development model uses six interactions, namely interactions between students and lecturers, students with material, lecturers with material, students with students, lecturers with other lecturers, and material with material, through synchronous/asynchronous media. The results of this research show that the product developed is very suitable to be implemented to support online practical learning for core courses in higher education. This research has produced an online learning model for core subject practice with a flexible blended learning strategy at a low cost for students of the Mechanical Engineering Education Study Program. The resulting conclusion is that this model has the advantage of being able to create an online collaborative work environment. Validation by experts is carried out qualitatively and quantitatively.